(untitled) (Nepal Journal of Environmental Science, 2020)
Rising atmospheric CO2 and temperature are altering ecosystems’ carbon cycle. Soil respiration is a potential natural source of atmospheric CO2, an important terrestrial process to characterize soil as a carbon source or sink. Research carried was out in Annapurna Conservation Area (ACAP) as climate change poses special problems for mountain protected areas. Nepal has targeted to reduce the emissions resulting from land-use change by enhancing forest carbon stock by 5% above the 2015 level within 2025. In this case, identifying, quantifying and addressing different potential emission sources are very important. Soil respiration is the process of measuring natural carbon emissions from soil. The study in ACAP soil carbon emission from the forest, grassland, and agricultural lands was investigated using the close chamber method. The global temperature rise has been set to a global 2 °C below the preindustrial period by the IPCC. The rise in temperature has a positive feedback response over soil respiration by increasing CO2 emission. The study shows the potential simulation of soil CO2 emission by 0.217 mg m-2 m-1 in the forest, 0.359 mgm-2 m-1 in grassland, and 0.457 mg m-2 m-1 in agricultural land in October in ACAP.